2001
DOI: 10.1259/bjr.74.888.741121
|View full text |Cite
|
Sign up to set email alerts
|

Cancers detected and induced, and associated risk and benefit, in a breast screening programme

Abstract: Current cancer detection rates and dose levels in the UK Breast Screening Programme are used to compare numbers of cancers detected with numbers predicted to be induced by the screening process itself. Numbers of those detected are shown to exceed those induced by a large margin for women aged over 50 years. The associated benefit/risk ratio is also considered. For younger women this margin is progressively reduced but remains positive at least down to age 40 years, and possibly beyond. Women both with and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 6 publications
0
24
2
Order By: Relevance
“…A two-view mammogram, i.e., two photos per breast, uses 4 mGy average radiation dose. 5 The breast cancer induction risk due to mammography radiation was 0.0000165 under the age of 50, and 0.0000114 over the age of 50 (28).…”
Section: Valuesmentioning
confidence: 99%
“…A two-view mammogram, i.e., two photos per breast, uses 4 mGy average radiation dose. 5 The breast cancer induction risk due to mammography radiation was 0.0000165 under the age of 50, and 0.0000114 over the age of 50 (28).…”
Section: Valuesmentioning
confidence: 99%
“…The estimated risk associated with radiation will depend on whether a linear or quadratic dose response model is chosen, and on whether an additive or relative risk model is used. The average radiation dose for mammography has reduced considerably over the past 15-20 years, and most recent studies have estimated that the benefit of screening is likely to outweigh the risk even in younger women (Law and Faulkner, 2001). Estimates of the average received dose in the UK Age trial are of 2.5 mGy per oblique film and 2.0 mGy per craniocaudal film (Young, 2001); in this study, age was not found to be a significant factor affecting the dose to screened women aged above or below 50 years.…”
Section: Exposure To Radiationmentioning
confidence: 99%
“…Because stage of the disease at diagnosis is associated with prognosis, efficient diagnostic tools for early detection are keys to survival. Although mammography is the most reliable way to detect breast cancer, it has some limitations (2)(3)(4). Biopsy is the method used to establish a definitive diagnosis, but it is an invasive procedure.…”
mentioning
confidence: 99%